Separation of power between the judiciary bodies and executive bodies in Malaysia: a legal critics and suggestions to reform / Al Norizwan Kariwon … [et al.] - Kariwon, Al Norizwan; Zahari, Muhammad Daniel Haqim; Solidau, Joel Joannes; Mohamed Hashim, Tengku Mohamed Harith (Faculty of Law, 2010)
This research aims to explore the constitutional laws on the doctrine of separation of power based on Federal constitution. It is to look into the practice of separation of power where it could highlight the interaction of law with other aspects of life such as economic, social and political development of the country. It also help to highlight the mechanism in preserving the fundamental liberties in protecting the citizens as stated in Federal Constitution under article 5 until article 13. Furthermore, the research also looks into the practical standpoint, which this research of this nature would provide the information about the extent of the issue or problem in the practice of separation of power. The research would also be able to provide better understanding for the societies in the said concept of separation of power. In addition the study will delve into the importance and the implication of reforming the doctrine of separation of power in various aspects especially on economic, politically and social.